2014
DOI: 10.1371/journal.pone.0097341
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin Dampens High-Fructose Corn Syrup-Induced Hepatic Manifestations of the Metabolic Syndrome in a Murine Model

Abstract: Hepatic manifestations of the metabolic syndrome are related obesity, type 2 diabetes/insulin resistance and non-alcoholic fatty liver disease. Here we investigated how the anti-inflammatory properties of lactoferrin can protect against the onset of hepatic manifestations of the metabolic syndrome by using a murine model administered with high-fructose corn syrup. Our results show that a high-fructose diet stimulates intestinal bacterial overgrowth and increases intestinal permeability, leading to the introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 55 publications
(50 reference statements)
0
23
0
Order By: Relevance
“…Recently, these bioactive components have gained interest because of their notable anti-hypertensive, antioxidant, anti-inflammatory and hypercholesterolaemia effects [4, 5]. A few studies, mainly in animals, suggested the potential benefits of exogenous Lf against lipid disorders, insulin signalling disturbances and inflammation [1214]. The central message of this work, as mentioned above, relates to the independent relationship between concentrations of circulating Lf and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, these bioactive components have gained interest because of their notable anti-hypertensive, antioxidant, anti-inflammatory and hypercholesterolaemia effects [4, 5]. A few studies, mainly in animals, suggested the potential benefits of exogenous Lf against lipid disorders, insulin signalling disturbances and inflammation [1214]. The central message of this work, as mentioned above, relates to the independent relationship between concentrations of circulating Lf and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This iron-binding glycoprotein possesses antimicrobial activity and it also improves immune defences against pathogenic bacteria and viruses [11]. In addition, Lf was shown to lower inflammation, oxidative stress (OxS) and apoptosis, which are key mechanisms involved in the progression of various cardiometabolic disorders [1214] while few reports have emphasized its anti-adipogenic actions [15, 16]. Accordingly, Moreno-Navarrete et al proposed that endogenous Lf biosynthesis is essential to achieve adequate adipogenesis [17].…”
Section: Introductionmentioning
confidence: 99%
“…To date, antimicrobial properties, modulation of lipid metabolism, anti-cancer properties, and ability to increase hemoglobin and serum iron ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 16 concentrations have all been recognized (Brock 2002;Marnila P 2009). Animal studies have shown reduced hepatic cholesterol, plasma triglycerides and non-esterified fatty acids (Takeuchi et al, 2004); enhanced weight loss, suppressed weight regain, improved glucose tolerance and decreased adipose tissue inflammation (Shi J 2011); and improved glucose homeostasis (Li et al, 2014) Of further interest is the randomized double-blind placebo-controlled trial by Ono et al which examined the effect of daily supplementation with 300mg enteric coated bLf over an eight week intervention in 26 Japanese adults considered to be abdominally obese (visceral fat area >100cm 2 ). Supplementation with bLf resulted in a significant decrease in visceral fat accumulation by 14.6cm 2 (p=0.0089), as well as body mass index (-0.6kg/m2), hip circumference (-2.6cm) and body weight (-1.5kg) compared to placebo, in the absence of lifestyle change (Ono et al, 2010).…”
Section: Health Benefitsmentioning
confidence: 99%
“…Some studies have indicated that antibiotics, prebiotics, and probiotics are protective factors in fructoseinduced liver damage (136)(137)(138)(139). These studies suggested that gut microbe manipulation may protect from the side effects of high-fructose diets on the liver.…”
Section: Introductionmentioning
confidence: 99%